KUALITAS PELAYANAN NASABAH PADA BANK RAKYAT INDONESIA UNIT VETERAN CABANG PALU - Abbas, Muhammad Reza (Katalogis, 2016)
The aim of this research is to analyze the quality of customer service in providing loans to its costumers. The number of informants in this study was ten people consisting of six employees and four customers. Technique used in determining the informants was purposive sampling method that the informants were selected deliberately. Data collecting techniques in this study were observations, interviews, and documentations. The result shows that the quality of customer service in providing loans at Veteran Unit of Palu Branch Office of BRI had not been carried out optimally because it had not satisfied its costumers in delivering credit service. This was proven with five indicators which became the parameter in this research where there were two aspects it had not fulfilled well; they were reliability that the employees need more training from Bank Rakyat Indonesia to support the service delivery and there were some of its employees that could not provide good sense of security in collecting debt of the costumers in arrears, another obstacle was assurance that some costumers did not punctually fulfill their responsibility of the credit requirements. The other three indicators like responsiveness, empathy, and tangible already supported the service quality optimally at the Bank Rakyat Indonesia at Veteran Unit of Palu Branch Office.Â